The Light and Scanning Electron Microscopic Structure of the Papilla Vallatae in the Porcupine (Hystrix cristata) - Atalar, Omer; Karan, Meryem (Medwell Online, 2011)
This study was aimed to examine detailed structure of papilla vallata in porcupines by light and scanning electron microscopy. For this purpose, 5 mature porcupines (3 males and 2 females) were used. Papilla vallata was one each in both side of median line in dorsal surface of tongue base. There was taste buds (Caliculus gustatorius) only inner wall of ditch of papilla. Maximum 9 taste buds were counted on one side. The mean surface area of papilla ditch wall was calculated as 30.26 mm(2). In addition, mean micrometric measurements of papilla vallata were width of papilla (3225 pm), length of papilla (1875 pm), depth of ditch (1890 pm), length of the taste bud (206.25 mu m), width of the taste bud (117.86 mu m) and epithelial thickness (362.5 mu m). Two types of taste bud cells that were lightly dyed (Epitheliocytus sensorius gustatorius) and densely dyed (Epitheliocytus sustentans) were observed as arranged vertically through depth of ditches. The borders of surface epithelial cells of papilla vallata were clearly observed on scanning electron microscope. There were micropits and microridges on cell surfaces. In conclusion, papilla vallata of porcupines were examined in detail by light and scanning electron microscopy and then the similarities and differences with other mammals were determined.
Keywords: Porcupine; papilla vallata; scanning electron microscopy; taste buds; mammals; Turkey